A Differential Boundary Operator of the Sturm–Liouville Type on a Semiaxis with Two-Point Integral Boundary Conditions - Mylyo, O. Ya.; Storozh, O. G. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove that a differential boundary operator of the Sturm–Liouville type on a semiaxis with two-point integral boundary conditions that acts in the Hilbert space L 2(0, ∞) is closed and densely defined. The adjoint operator is constructed. We also establish criteria for the maximal dissipativity and maximal accretivity of this operator.